Estimation of car air resistance by CFD method - Tuan, Phan Anh; Quang, Vu Duy (Vietnam Journal of Mechanics, 2014)
Total car resistance is including rolling resistance and air resistance. Rolling resistance comes from car tires when it rolls over the roads with car weight. Air resistance comes from the body when it moves in the air with car body surface area. The air resistance of a car depends upon its shape. The bigger the surface area of a car body, the more air molecules the car will hit and so the larger the air resistance. This paper will mention to estimation of car air resistance by computational fluid dynamics (CFD) method. A 3D car body has used for simulation in ANSYS FLUENT CFD software. The k-\(ε\) turbulence model and segregated implicit solver was used to perform computation in this study.